2014
DOI: 10.1097/ncc.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Initial Levels and Trajectories of Anxiety in Women Before and for 6 Months After Breast Cancer Surgery

Abstract: Background The diagnosis of breast cancer in combination with the anticipation of surgery evokes fear, uncertainty, and anxiety in most women. Objective In patients who underwent breast cancer surgery, study purposes were to examine how ratings of state anxiety changed from the time of the preoperative assessment to 6 months after surgery and to investigate whether specific demographic, clinical, symptom, and psychosocial adjustment characteristics predicted the preoperative levels of state anxiety and/or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 73 publications
6
29
0
5
Order By: Relevance
“…Perception of greater overall social support predicted greater quality of life and fewer depressive symptoms but did not predict psychological distress . A sense of isolation predicted higher levels of anxiety in 1 study . Support from physician predicted better quality of life .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Perception of greater overall social support predicted greater quality of life and fewer depressive symptoms but did not predict psychological distress . A sense of isolation predicted higher levels of anxiety in 1 study . Support from physician predicted better quality of life .…”
Section: Resultsmentioning
confidence: 73%
“…Appraisals and illness perceptions of this type are widely viewed as important determinants of reactions to stress . Perceived control predicted less psychological distress and lower anxiety . One study did not find any association between perceived control and psychological distress .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The trend toward improvement across non-memory-related domains over time is consistent with a recent meta-analysis which found that when assessing studies of cognition in women with breast cancer with a longitudinal design, long-term memory was the only cognitive domain to produce a significant mean effect size ( d = 0.41); this finding indicates that chemotherapy patients typically exhibited improvements in long-term memory when studied prior to chemotherapy and over time (Ono et al 2015). However, an alternate explanation is that cognitive performance at baseline may have been lower than usual as a result of emotional distress (Pérez et al 2014), recovery from surgery (Kyranou et al 2013), and anxiety over the initiation of chemotherapy (Lyon et al 2015). Further, it is also possible that baseline deficits in cognitive performance observed prior to the initiation of chemotherapy reflect the interactive effects of pre-morbid factors including comorbid medical conditions (Mandelblatt et al 2014), systemic inflammation (Cheung et al 2015), residual anesthesia effects (Ramaiah and Lam 2009), and/or individual differences in cognitive and physiological reserve (Opdebeeck et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, single assessments of anxiety and depressive symptoms were used to diagnosis CADS. However, significant heterogeneity exists in the trajectories of anxiety and depressive symptoms over the course of patients’ cancer treatment (Kyranou et al, 2014a; Kyranou et al, 2014b). …”
Section: Introductionmentioning
confidence: 99%